NEO KUá¹†á¸ŒALINÄª YOGA DALAM UPAYA MENUMBUHKAN KECERDASAN SPIRITUAL DI YAYASAN ANAND ASHRAM - Putu Sriasih, Kadek Hemamalini (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2020)
This study discusses Ananda's Neo Ku??alin? Yoga as an Effort to Grow Spiritual Intelligence at the Anand Asrham Foundation. This research is a descriptive research (descriptive research) using the descriptive field method. This study tries to reveal how Ananda's Neo Ku??alin? Yoga practice can make a person become spiritually intelligent. Ku??alin? is a very extraordinary energy found in humans, unfortunately not many people are aware of this, if this energy is successfully raised then every human being is able to optimize abilities that should be possessed as humans. One way to get that energy to rise is by yoga. In this case the yoga carried out at the Anand Ashram Foundation is combining exercises developed from the yoga tradition that will lead to entering the seven stages of the development of chakras with illustrations of Vyayam: 8 warm-up exercises, pr???y?ma 6 breathing exercises, and ?sana,: 19 yoga postures. By doing routine and consistent exercises yoga participants will not only be physically healthy and also be flexible but also be spiritually intelligent because participants are not only equipped with ?sana training, but also taught how to make yoga a way of life, so that the benefits of yoga can be applied optimally in everyday life. With the growth of a spiritual attitude, yoga participants have the ability to find awareness and through relationships / interactions with the main forces in the form of energy from those who create the source. So with the rise of energy Ku??alin? participants can become humans who have spiritual intelligence. Yoga, Ku??alin?, intelligence, spiritual.